Identifying the Prevalence, Trajectory, and Determinants of Psychological Distress in Extremity Sarcoma - Melissa Tang; David Castle; Peter Choong (2015)
Objective. Extremity sarcoma (ES) is a rare cancer that presents with unique challenges. This study was performed to identify the prevalence, trajectory, and determinants of distress and characterise sources of stress in this cohort. Methods. Consecutive patients with ES were prospectively recruited between May 2011 and December 2012. Questionnaires were administered during initial diagnosis and then six months and one year after surgery. Results. Distress was reported by about a third of our cohort and associated with poorer physical function, poorer quality of life, and pain. In addition to fears regarding mortality and life role changes, the most common sources of stress were centered on dissatisfaction with the healthcare system, such as frustrations with a lack of communication with the hospital regarding appointments and lack of education regarding management and outcomes. Conclusions. Psychological distress presents early in the cancer journey and persists up to one year after surgery. Distress is associated with negative outcomes. Active screening and effective interventions are necessary to improve outcomes. Sources of stress have been identified that may be amenable to targeted interventions.